Cancer Preventive and Therapeutic Potential of Banana and Its Bioactive Constituents: A Systematic, Comprehensive, and Mechanistic Review - Mondal, Arijit; Banerjee, Sabyasachi; Bose, Sankhadip; Das, Partha Pratim; Sandberg, Elise N.; Atanasov, Atanas G.; Bishayee, Anupam (Frontiers in Oncology, 2021)
Background: The banana (Musa spp.) plant produces elongated and edible fruit. The two main parthenocarpic species of banana are Musa accuminata Colla and Musa balbisiana Colla. There are several health-promoting and disease-preventing effects of Musa accuminata Colla, which are attributed to its important bioactive compounds, including phenolics, carotenoids, biogenic amines, phytosterols, and volatile oils, found in the stem, fruit, pseudostem, leaf, flower, sap, inner trunk, root, and inner core. Banana possesses numerous pharmacological activities, such as antioxidant, immunomodulatory, antimicrobial, antiulcerogenic, hypolipidemic, hypoglycemic, leishmanicidal, anthelmintic, and anticancer properties. Various individual studies have reported anticancer effects of different components of the banana plant. However, according to our understanding, an up-to-date, systematic, and critical analysis of existing scientific results has not yet been carried out. Objectives: This review aims to include a thorough assessment of banana and its phytochemicals for cancer prevention and therapy with a focus on cellular and molecular mechanisms of action. Methods: The available research studies on anticancer activities of banana extracts, fractions and pure compounds were collected using various scholarly databases, such as PubMed, ScienceDirect, and Scopus, based on predetermined selection criteria. Results: Various banana extracts, fractions, and phytoconstituents, including ferulic acid, protocatechualdehyde, 2-pentanone, 4-epicyclomusalenone, cycloeucalenol acetate, and chlorogenic acid, have been shown to exhibit cancer preventative and anticancer activities in breast, cervical, colorectal, esophageal, hepatic, oral, prostate, and skin cancers. Bioactive components present in bananas have exhibited antiproliferative, cell cycle arrest-inducing, apoptotic, anti-adhesive, anti-invasive, and antiangiogenic effects through modulation of diverse, dysregulated oncogenic signaling pathways. Conclusion: Based on the critical analysis of available literature, banana products and phytoconstituents show enormous potential for future development of drugs for cancer prevention and therapy. However, more mechanistic studies and well-designed clinical trials should be performed to establish its efficacy.